Mathematical Concept Teaching Design based on APOS Theory in the Context of Mathematical History: A Plane Rectangular Coordinate System as an Example - Xiang, Zhang An; Pereira, Jerito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
Mathematics learning aims to train students to observe, think, and express the real world with mathematical vision. However, in the traditional static concept teaching mode, teachers tend to use the concept formation or expository method, so most students cannot understand abstract concepts in class but have to do exercises to consolidate their understanding of concepts, which does not meet the requirements of cultivating talents with core mathematical literacy. Literature research method: To understand the current research status of APOS theory on mathematics concept teaching at home and abroad, this study consulted relevant books, journals, papers, and network resources at home and abroad. This paper discusses it based on the history of mathematics and provides practical guidance for teachers on designing student-centered teaching activities based on APOS theory. Based on the teaching design under the APOS theory, problem-solving is used to gradually guide students to abstract mathematical concepts and learn to think about the real world with mathematical thinking. Teachers will also diagnose students' learning stages through problem-solving situations and constantly debug math classes suitable for students. In guiding students to think, explore and interact, teachers create cognitive conflicts many times, encourage students to question questions, and give full play to students' subjectivity.